2011
DOI: 10.1103/physreva.84.011807
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the mechanical action of light

Abstract: We demonstrate that the mechanical action of light manifests itself in the perceived topography measured with a scanning probe microscope. This modality of sensing optically induced forces opens up possibilities to quantify properties of electromagnetic fields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…Consequently, the averaged surface-induced force is relatively small because the surface forces depend strongly on the tip-sample separation. Thus, in these conditions the magnitudes of OIF become comparable to the surface forces present in typical experimental conditions [11,56,58,59].…”
Section: Effect Of Optically Induced Forcesmentioning
confidence: 58%
See 3 more Smart Citations
“…Consequently, the averaged surface-induced force is relatively small because the surface forces depend strongly on the tip-sample separation. Thus, in these conditions the magnitudes of OIF become comparable to the surface forces present in typical experimental conditions [11,56,58,59].…”
Section: Effect Of Optically Induced Forcesmentioning
confidence: 58%
“…As the probe passes over the illumination, the total force gradient acting on the probe is increased because of the probe's exposure to the additional attractive contribution of the optical force gradient. The scanning system's feedback retracts the probe to reduce the contribution from the surface forces, thus maintaining a constant force gradient acting on the probe [11]. As a result, a topographic feature is recorded, which correlates with the field distribution across the surface.…”
Section: Optical Topographymentioning
confidence: 99%
See 2 more Smart Citations
“…The third is the development of normal force tuning-fork feedback which shows that the ultimate in force sensitivity with glass based multiprobes enabled probes for NSOM, electrical, thermal, plasmonic, ion conductance, fountain-pen nanolithography, and scanning electrochemical microscopy applications (http://www.nanonics.co.il/ products/spm-probes-and-nanotools.html). For example it has been shown that with such probes and the platform used in the present study, a force sensitivity of 1.6 pN could be achieved, which is more sensitive than any other AFM based feedback technique developed thus far [16].A major challenge that is pervasive in nearly all functional applications that include SPM is that the functional probes associated with these applications do not always achieve the ultimate in AFM topographic resolution. This is due to the additional dimensions inherent in some functional probes that are based on AFM feedback.…”
mentioning
confidence: 97%